1979
DOI: 10.1039/c39790000559
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a G·U base pair to the stability of a short RNA helix

Abstract: Variable temperature lH n.m.r. spectroscopic studies have shown that the contribution of an internal G-U base pair approximates that of an A.U base pair in the stability of a short RNA helix, THE existence of G-U base pairs was first proposed in the wobble hypothesis of Crick1 to explain the codon-anticodon interactions between mRNA and tRNA. This base pair has since been included in the proposed secondary structures of several native R N A S ~~~~Q despite the fact that several physical studies on the existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There is no NOE evidence for a second GU base pair in the spectrum to account for G18-U65 in Figure 1. Given that Watson-Crick base pairs at helix termini are often difficult to observe due to exchange broadening [e.g., see Chou et al (1984)] and that GU's are believed to be no stronger than AU Watson-Crick pairs (Romaniuk et al, 1979), the absence of NOE evidence for another GU is not surprising.…”
Section: Resultsmentioning
confidence: 99%
“…There is no NOE evidence for a second GU base pair in the spectrum to account for G18-U65 in Figure 1. Given that Watson-Crick base pairs at helix termini are often difficult to observe due to exchange broadening [e.g., see Chou et al (1984)] and that GU's are believed to be no stronger than AU Watson-Crick pairs (Romaniuk et al, 1979), the absence of NOE evidence for another GU is not surprising.…”
Section: Resultsmentioning
confidence: 99%
“…It probably accounts for the stability of the poly(G)·poly(V) double helix (582) and was found to approximate, in a complementary double-helical oligonucleotide, an A-V base-pair in stabilizing efficiency (583). As for the long A-I base-pair, it could be verified in the all-purine double-helix poly(A)'poly(I) (Chapter 13).…”
Section: ' 3'mentioning
confidence: 94%
“…though there are limited studies on the effect of internal G-U mismatches on duplex stability (Uhlenbeck et al, 1971;Lomant & Fresco, 1975;Romaniuk et al, 1979a,b; Alkema et al, 1982), no experiments have been reported on the effect of terminal G-U mismatches on oligonucleotide stability. We report below thermodynamic parameters of helix formation for four oligoribonucleotides containing terminal G-U mismatches.…”
mentioning
confidence: 99%